LEXICAL AND SEMANTIC CHARACTERISTICS OF LEGAL DOCUMENTS IN DIFFERENT FOREIGN LANGUAGES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article discusses the lexical and semantic features of legal documents in English, identifies linguistic phenomena that must be taken into account when translating documents, it is important to translate correctly. Based on functional, structural and semantic characteristics, a definition of a legal term is given, according to which it is proposed to understand a word or phrase used in the operation of a legal business style. formal language, expressing the main concept of a legal norm, having clear semantic boundaries, tight lexical compatibility. Translations of single- and multi-component legal terms based on the functional and stylistic identity of the term's components, the attributes of the word being defined, the analysis of semantic links between the components. parts of word combinations and their division into semantic groups, the concatenation is analyzed.